2006
DOI: 10.1111/j.1468-2389.2006.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Nonverbal Impression Management Tactics in Behavior Description and Situational Interviews

Abstract: This study investigated how structured interview formats, instructions to convey favorable impressions, and applicants' individual differences influenced the use and effectiveness of verbal and nonverbal impression management (IM). Results from 190 people who were screened for a training program demonstrated that interview format affected the kind of tactics used, which in turn positively influenced interviewer evaluations. Behavior description interviews triggered self-focused (and defensive) tactics, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 107 publications
3
109
1
1
Order By: Relevance
“…Past research has shown that the use of specific IM behaviors in structured interviews is a meaningful function of the interview requirements (Ellis et al, 2002) and of stable personality differences (Peeters & Lievens, 2006;Van Iddekinge et al, 2007). Being a meaningful expression of a candidate's personality, we argue that IM behavior represents a relatively stable behavioral expression or manifestation of individuals' behavioral style.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Past research has shown that the use of specific IM behaviors in structured interviews is a meaningful function of the interview requirements (Ellis et al, 2002) and of stable personality differences (Peeters & Lievens, 2006;Van Iddekinge et al, 2007). Being a meaningful expression of a candidate's personality, we argue that IM behavior represents a relatively stable behavioral expression or manifestation of individuals' behavioral style.…”
mentioning
confidence: 77%
“…In combination, results from these few studies (Ellis et al, 2002;McFarland et al, 2002;Peeters & Lievens, 2006;Stevens & Kristof, 1995;Van Iddekinge et al, 2007) suggest that (a) interviewees show more assertive than defensive IM behaviors, (b) interviewees rely more heavily on ingratiation when answering future-oriented questions and rely more heavily on self-promotion when answering past-oriented questions, and (c) the use of these assertive techniques leads to a better evaluation by the interviewers. Because, there is very limited published research in this area, as previously stated, we tried first to reproduce these results as a basis for subsequent novel assumptions.…”
Section: Im Behavior In Structured Interviewsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, further analysis showed that externals use internal-controllable justifications, beside external-uncontrollable ones, equally as a defensive strategy against interviewers who perceive external-uncontrollable attributions as conveyers of negative impressions. Peeters and Lievens (2006) reported no significant correlation between internal locus of control and self-focused IM tactics. However, the correlation between external locus of control and defensive IM tactics was significant.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 91%
“…Research on impression management has been robust in areas such as assessment and job interviews (Peeters & Lievens, 1986), business ethics (Giacalone & Payne, 1987), and personal space invasions (Rosenfield, Giacalone & Kennedy, 1987). Of late, organisational literature on impression management has been trickling in.…”
Section: Review Of Related Literaturementioning
confidence: 99%